Enhancing Engineering Education through Drone Technology Skilling Program: Analyzing the Impact on Program Outcomes - Beldar, Pankaj R.; Munje, Ravindra K.; Kadbhane, Snehal V. (Journal of Engineering Education Transformations, 2025)
The interdisciplinary skilling program at the AICTE IDEA Lab focused on drone technology aimed to enhance the achievement of Program Outcomes (POs) for engineering students. Over six days, students engaged in activities like rapid prototyping, simulation-based learning, and AI-driven automation. These methods targeted critical POs, including engineering knowledge, problem-solving and modern tool usage. The program utilized direct assessments (tests conducted after each module) and indirect assessments (student feedback) to measure PO attainment, both rated at level 3. Collaborative hands-on projects, peer teaching, and real-world applications enabled students to bridge the gap between theoretical learning and practical skills. Positive feedback highlights the program's success in fostering interdisciplinary competencies and preparing students for technological challenges.